2020
DOI: 10.21203/rs.3.rs-20050/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of the complete chloroplast genome of seven Nymphaea species

Abstract: Background: Although there has been a long history of cultivation and research on Nymphaea, the taxonomic relationships and evolutionary relationships among Nymphaea species remain controversial. The chloroplast (cp) genome can provide a new method to determine species origin, evolution, and phylogenetic relationships of Nymphaea. However, there are few studies on the cp genomes of Nymphaea, and the data of their genomes are very scarce. The complete cp genomes of seven Nymphaea species were sequenced by high-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our results suggested that the low expression of RALF, UTG and G-type lecRLK in self-pollination treatments was one of the main reasons why pollen tubes stopped growing and failed to fertilize. Cytochrome P450 has wide-range catalytic activity and is involved in the synthesis and metabolism of sterols, terpenoids, fatty acids, alkaloids, isoflavones, flavonoids and plant hormones (Sun et al, 2019). In our study, three cytochrome P450 87A3-like genes (CYPs) were identified as candidate hub genes selected by WGCNA, and the expression of CYPs in cross-pollination was significantly higher than that in self-pollination.…”
Section: Tfs and Hub Genes Related To Lsi Selected By Wgcnamentioning
confidence: 82%
See 1 more Smart Citation
“…Our results suggested that the low expression of RALF, UTG and G-type lecRLK in self-pollination treatments was one of the main reasons why pollen tubes stopped growing and failed to fertilize. Cytochrome P450 has wide-range catalytic activity and is involved in the synthesis and metabolism of sterols, terpenoids, fatty acids, alkaloids, isoflavones, flavonoids and plant hormones (Sun et al, 2019). In our study, three cytochrome P450 87A3-like genes (CYPs) were identified as candidate hub genes selected by WGCNA, and the expression of CYPs in cross-pollination was significantly higher than that in self-pollination.…”
Section: Tfs and Hub Genes Related To Lsi Selected By Wgcnamentioning
confidence: 82%
“…and Theobroma cacao, in which the pollen tube can grow successfully in the styles, but the inhibition occurs either prezygotically or postzygotically (Hao et al, 2012). Many studies have been performed to identify the key factors involved in the LSI response, but the mechanism remains unclear (Chen et al, 2012;Sun et al, 2019). The genetic basis of LSI was hypothesized to be gametophytic under genetic control (Zhou and Zheng, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…GC content is an important genomic and systematic character that describes the nucleotide proportions in the genome. When GC content in the genome is greater, it has a greater density of DNA bases, making the sequence more stable and difficult to mutate (Sun et al, 2021). The overall GC content of the eight plastomes varied from 38.3% to 39.1% (Table 1) and was clearly lower than the AT content.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of cp is generally maternal inheritance; there is no problem of gene recombination ( Li et al., 2014 ; Zhao et al., 2015 ). In recent years, the cp genome has been mainly used in phylogenetic, population genetics, and phylogeography studies ( Wang et al., 2022b ), in which plant phylogenetic analysis is the most basic cp genome analysis, which has been widely used in the phylogenetic study of the plant kingdom or one of the groups and to identify the relationships of angiosperm order, family, genus, interspecies, and intraspecies ( Sun et al., 2020 ; Guo et al., 2021 ; Li et al., 2021 ; Xie et al., 2021 ; Liu et al., 2022 ; Raman et al., 2022 ; Wang et al., 2022a ). The cp genome has unique advantages in plant phylogenetic studies.…”
Section: Introductionmentioning
confidence: 99%